Search for anomalous couplings in the Higgs sector at LEP - Dova, María Teresa (2000)
We search for a Higgs particle with anomalous couplings in the eqeyaHg, eqeyaHZ and eqeyaHeqey processes with the L3 detector at LEP. We explore the mass range 70 GeV-m -170 GeV using 176 pby1 H of integrated luminosity at a center-of-mass energy of 's s189 GeV. The Higgs decays Habb, Hagg and HaZg are considered in the analysis. No evidence for anomalous Higgs production is found. This is interpreted in terms of limits on the anomalous Z couplings d, d , Dg and Dk . Limits on the G Ž .Ž . Hagg and G HaZg partial widths in the explored Higgs mass B 1 g range are also obtained. q 2000 Elsevier Science B.V. All rights reserved.